Uptake of genetic counselling services by patients with cystic fibrosis and their families - S. Macaulay; N. Gregersen; A. Krause (South African Family Practice)
Background: Although cystic fibrosis (CF) is a common genetic condition, genetic counselling services appear to be underutilised by affected families. The aim of this study was to determine the uptake of genetic counselling and mutation testing for CF by relatives of affected individuals, and the impact of introducing hospital-based genetic counselling services.